Development of gurindam twice teaching materials in the pancasila education subject to improve cross culture understanding knowledge at MTs Negeri Tanjungpinang - Andhika Joelystiar; Sukriono, Didik; Untari, Sri (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2026)
This study aims to develop Gurindam Dua Belas teaching materials in the form of an E- Book in the Pancasila Education subject to improve students' Cross Culture Understanding knowledge at MTs Negeri Tanjungpinang. The background of this study is the suboptimal use of local wisdom in Pancasila Education learning and the low understanding of students towards cross-cultural values. This study uses the Hannafin and Peck research and development method, which includes three main stages: needs analysis, design, development and implementation, accompanied by evaluation at each stage. The research subjects involved students of MTs Negeri Tanjungpinang. Data collection techniques used expert validation questionnaires, student and teacher response questionnaires, and pretest and posttest tests to measure the increase in Cross Culture Understanding knowledge. Data were analyzed descriptively quantitatively and qualitatively. The results of the study showed that the Gurindam Dua Belas E-Book developed was declared valid by material and media experts, and practical based on student and teacher responses. The effectiveness test showed an increase in students' Cross Culture Understanding knowledge as indicated by a significant difference between pretest and posttest scores with a moderate increase category. Thus, it can be concluded that the Gurindam Dua Belas E-Book teaching material developed through the Hannafin and Peck model is suitable and effective for use as an alternative teaching material in the Pancasila Education subject to improve students' cross-cultural understanding.